Upaya Meningkatkan Motivasi dan Hasil Belajar Siswa pada Mata Pelajaran IPS melalui Pendekatan Cooperative Learning Tipe STAD di MTs Negeri 1 Indramayu - Suwanda Saputra (Jurnal Pendidikan Madrasah, 2021)
This research aims to find out the effectiveness of the application of cooperative learning (CL) approach type STAD in an effort to increase the motivation to learn mathematics of students Class IX-C MTs Negeri 1 Indramayu. This research uses action research methods carried out in two cycles, each cycle covering planning, implementation, observation and reflection activities. The final results of the action in cycle II showed that the teacher's observation results obtained an average score (4.43) and the student's observation result reached an average score (4.32). While the impact of increasing learning motivation is the increasing acquisition of student learning outcomes reaching an average score (82.60), meaning that the success indicator (>4.0) has been exceeded. Because the success indicator has been proven the research is declared successful and stopped in cycle II.